New Perspectives in the Studies on Endocannabinoid and Cannabis: A Role for the Endocannabinoid-Arachidonic Acid Pathway in Drug Reward and Long-Lasting Relapse to Drug Taking - Tsuneyuki Yamamoto; Kusnandar Anggadiredja; Takato Hiranita (Elsevier, 2004)
Growing evidence on the involvement of cannabinoids in the rewarding effects of various kinds of drugs of abuse has suggested that not only the classical dopaminergic and opioidergic, but also the most recently established endocannabinoid system is implicated in the brain reward system. Furthermore, the interplay between the three systems has been shown to be an essential neural substrate underlying many aspects of drug addiction including craving and relapse. Relapse, the resumption of drug taking following a period of drug abstinence, is considered the main hurdle in treating drug addiction. Yet, little is known about its underlying mechanisms. The link between the endocannabinoid system and the arachidonic cascade is currently being clarified. While several findings have, indeed, shown the essential role of the endocannabinoid system in the reinstatement model, the endocannabinoid-arachidonic acid pathway may also be an important part in the neural machinery underlying relapse. This evidence may provide an alternative approach that will open a novel strategy in combating drug addiction. Keywords:: drug seeking behavior, relapse, addiction, endocannabinoid system, arachidonic acid cascade